Educação musical em contextos Montessori: narrativas de professores de música - Mengarda, Beatrís Schmidt Faraco (2024)
This research proposal presents research linked to the Graduate Program in Education, within the Education and Arts research line, and the NarraMus research group at the Federal University of Santa Maria. Its objective is to understand the challenges, dilemmas, and constructions that permeate the work of licensed music teachers within the context of Montessori Education. Additionally, it aimed to explore the professional practice of music teachers in Montessori schools and to understand the functioning of musical moments, concepts, and materials present in music classes within Montessori institutions, with a focus on early childhood education. In this regard, authors such as Beyer (2005), Fernandes (2020), Mateiro and Ilari (2012), Montessori (1965; 1984; 1987), and Pollard (1993) contributed to the discussions of this research. Methodologically, the investigation, of a qualitative nature (Bogdan & Biklen, 1994; Minayo, 2012), consists of narrative interviews (Ravagnoli, 2018; Jovchelovitch & Bauer, 2003; Souza, 2011). Data analysis was conducted based on transcriptions of the teachers' narratives (Josso, 2010). Furthermore, Souza's (2004; 2014) comprehensive-interpretative process, organized into three phases, provides the foundation for reflection. The research results highlight that, despite the challenges faced by music teachers in Montessori schools, their personal and formative trajectories, combined with a constant pursuit of study, updating, and reflection on practice, culminate in approaches that not only favor the development of children but also emphasize the importance of the prepared environment that stimulates autonomy and musical learning.